AB0482 A Prospective Study in Premenopausal Women with Systemic Lupus Erythematosus Supplemented with Two Different Regimens of Vitamin D: Efficacy and Safety at Twelve Months of Follow Up. (10th June 2014) - Dall'ara, F.; Andreoli, L.; Piantoni, S.; Piva, N.; Tincani, A.
Abstract : Background: Systemic Lupus Erythematosus (SLE) patients (pts) are at risk for low vitamin D (VitD) levels because of lack of sun exposure. The current strategies of VitD supplementation do not seem to be sufficient not only for the prophylaxis of osteoporosis, but perhaps also to bring out the immunomodulatory effects of VitD that were highlighted by some in vitro studies. Few prospective studies are available on the effects of VitD supplementation SLE pts. Objectives: To evaluate at 12 months of follow-up (T12) the efficacy, safety and the effects on SLE disease activity of an oral Cholecalcipherol supplementation given with 2 different regimens in a cohort of SLE pts. Methods: 34 premenopausal SLE women were enrolled. A group of 18 pts (group S) were given "standard" regimen of supplementation (Cholecalcipherol 25.000UI once/month).The other 16 pts (group I) were given an "intensive" regimen (Cholecalcipherol 300.000UI bolus, then 50.000UI once/month). The circulating levels of 25-OH VitD were dosed every 3 months with a chemiluminescence assay kindly performed by the manufacturer (DiaSorin S.p.A., Italy). Results: At baseline (T0) there was no significant difference in VitD levels in the 2 groups. After 3, 6, 9 and 12 months "group I" showed significantly higher VitD levels (median at T12: 32.0vs24.8 p=0, 04). There were no significant differences upon season of enrollment. At T0 there was no difference in the proportion of sufficient pts (>30 ng/ml) between groups (S:50%, I:56%), while at T12 sufficient pts were 28% in S and 75% in I (p=0.02). No significant variations in the levels of calcium, phosphorus and PTH were observed. No cases of PTH suppression. There were 3 cases of transitory mild hypercalciuria (2 in I, 1 in S). The pts had clinically quiescent disease (median SLEDAI 2 in S, 4 in I), but serologically active disease (positive anti-DNA and/or complement consumption in nearly 50% of the pts). No statistically significant variation in the titers of anti ds-DNA and in the levels of C3, C4, CH50 was observed at T12 in both groups. Conclusions: Intensive supplementation with VitD has a safe profile as the standard regimen but it is able to induce sufficient levels in a larger number of pts. No particular effects on serological SLE parameters was noted, probably due to the stable remission state of the pts. More data will come from the second year of the study in which patients will switch to the other group of supplementation. References: Cutolo M. et al.Vitamin D endocrine system and the immune response in rheumatic diseases. Vitam Horm.2011;86:327-51 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1825